Tipologi Renovasi Aksesibilitas Halte Trans Jogja - Harry Kurniawan (PLD UIN Sunan Kalijaga, 2014)
Trans-jogja is the latest transportation mode that gives new alternative for the mobility of people of Daerah Istimewa Yogyakarta (DIY). It is operated both for an alternative and also for improving the recent performance of public transportation mode and fulfilling several requirements that not facilitated yet. One of those essential requirement is the accessibility—the ease of reached and used by anyone.